2015
DOI: 10.1002/mus.24521
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb muscle impairment in myotonic dystrophy type 1: The need for better guidelines

Abstract: In myotonic dystrophy type 1 (DM1), leg muscle weakness is a major impairment. There are challenges to obtaining a clear portrait of muscle strength impairment. A systematic literature review was conducted on lower limb strength impairment in late-onset and adult phenotypes to document variables which affect strength measurement. Thirty-two articles were reviewed using the COSMIN guidelines. Only a third of the studies described a reproducible protocol. Only 2 muscle groups have documented reliability for quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Our results present strong evidence to support our previous hypothesis that pooling the results of both phenotypes for muscle strength would prevent the ability to properly assess the true level of muscle impairment for each phenotype. For example, a large descriptive study reported a loss of muscle strength of 40% in knee extensors, when all phenotypes were pooled.…”
Section: Discussionsupporting
confidence: 70%
“…Our results present strong evidence to support our previous hypothesis that pooling the results of both phenotypes for muscle strength would prevent the ability to properly assess the true level of muscle impairment for each phenotype. For example, a large descriptive study reported a loss of muscle strength of 40% in knee extensors, when all phenotypes were pooled.…”
Section: Discussionsupporting
confidence: 70%
“…Using PubMed, Medline, and CINAHL databases, the review of the literature of the past 20 years on muscular impairments in patients suffering from DM1 illustrates the lack of comparability studies and the questionable validity of the results with regard to undocumented metrological properties [29]. Most studies provide a general overview of the lower limb muscle impairments in patients affected by DM1, while only a few studies were devoted to the detailed description of this disorder and the related muscle impairments [30][31][32][33][34][35][36].…”
Section: Background Discussionmentioning
confidence: 99%
“…Myotonic dystrophy type 1 (DM1) is the most common form of inherited muscular dystrophy in adults, with an estimated prevalence between 0.9 patients per 100,000 individuals to 189 patients per 100,000 individuals depending on geographic location . DM1 is an autosomal dominantly inherited disorder, resulting from a mutation of unstable cytosine‐thymine‐guanine (CTG) base pairs repeats in the noncoding region of the myotonic dystrophy protein kinase ( DMPK ) gene on chromosome 19 . This mutation results in a complex, multisystem disorder that exhibits variable symptom presentation and rates of progression.…”
mentioning
confidence: 99%